(untitled) (Journal of Comparative & International Higher Education, 2023)
While critical scholars have attempted to decenter internationalization, limited research has aimed to understand internationalization efforts in the context of the socio-historical particularities of the postcolonial condition. This paper takes a decolonial perspective in the study of internationalization, in light of the Eurocentric tendencies of modernity, whose major manifestation in higher education is neoliberal globalization. We unpack internationalization in the U.S. and examine how it is embedded in and reproduces neoliberalism, racism, and colonialism. Since decolonization is not merely deconstructive but also regenerative, we reconceive what it means to be international and recommend how internationalization can be deployed as a tool of decolonization, considering various possibilities for hopeful and ethical praxis. We identify promising practices to spark ongoing reflection and action about ways to contest coloniality/modernity and rethink mobility. This paper can benefit educators seeking to reclaim internationalization and [re]align it with an ethos of mutuality and practices geared at strengthening cooperation, rather than competition.